Facial Aging Pattern of the Javanese Population in Indonesia: Contributions for Age Progression Analysis in Forensic Arts - Ana, Rizka Fitri; Alaydrus, Sayf Muhammad; Artaria, Myrtati Dyah; Chen, Yao-Fong (Biokultur, 2025)
The pattern of facial aging helps put the perception of age into face approximation from the skull, making the face more recognizable to the next of kin. The objective of this study is to determine the facial aging pattern of Javanese people in Indonesia. This study utilized the descriptive quantitative method to identify the highest frequency of the facial aging pattern variables according to its prominence (0 = Not visible; 1 = Slightly visible; and 2 = Clearly visible). This study involved 50 male and 50 female samples of the Javanese population. Each sexed samples were divided into two age-based groups: 40-44 and 45-49. The wrinkles on males and females aged 40-44 are mostly slightly or not visible. In the 45-49 age group, the wrinkles are visible on the forehead, eyes, and cheeks. Sex differences are found in the forehead and cheek grooves, with males having deeper wrinkles. Premature aging of the male samples might be caused by longer working hours and heavier smoking habits. Aside from sex and gender, ancestry also contributes to a unique aging pattern of the Javanese, differentiating them from other populations. The complex interaction between both sociocultural and biological factors is significant in forming a certain pattern of facial skin aging in different populations and sexes. Aside from its theoretical contribution to studies on human biological variations, this study can be referenced to depict more accurate and appropriate facial features in forensic cases that require facial approximations, especially those involving the Javanese people and the general Indonesian population.